Background, clinical features and treatment of attention deficit hyperactivity disorder in children. (October 2013) - Warikoo, Nisha; Faraone, Stephen V
Abstract : Introduction: Attention deficit hyperactivity disorder (ADHD) is an early onset, clinically heterogeneous, complex neurobiological disorder, defined by symptoms of inattention and hyperactivity/impulsivity and has been associated with a broad range of impairments for those affected. Additionally, ADHD in children and adolescents is frequently associated with psychiatric comorbidities. This review provides an overview of the epidemiology, neurobiology, genetics, diagnosis and most recent pharmacological approaches for treatment with a focus on safety and efficacy and describes the use of medications used to treat ADHD in special populations. Areas covered: PubMed, Cochrane database, Essential Evidence and Uptodate were searched for relevant articles about stimulant and non-stimulant pharmacological approaches in ADHD. Expert opinion: Data supporting the safety and efficacy of both stimulant and non-stimulant formulations have significantly grown over the past decade and more efforts are being made to tailor medications to the needs of the patients and their families. Pharmacogenomics research is evolving, but predictors of treatment response and side effects remain largely unknown. Other unmet clinical needs include long-term follow-up studies of the safety and efficacy of medications for those with ADHD alone, or with comorbidities and in special populations including preschoolers.